2003
DOI: 10.1002/jbm.a.10579
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bioactivity of silicon‐substituted hydroxyapatites

Abstract: Silicon-containing hydroxyapatites were synthesized by the controlled crystallization method. Chemical analysis, N(2) adsorption, Hg porosimetry, X-ray diffraction, scanning electron microscopy-energy-dispersive X-ray spectroscopy, and X-ray photoelectron spectroscopy (XPS) were used to characterize the hydroxyapatite and to monitor the development of a calcium phosphate layer onto the surface of the substrate immersed in a simulated body fluid, that is, in vitro bioactivity tests. The influence of the silicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
137
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(150 citation statements)
references
References 32 publications
12
137
1
Order By: Relevance
“…The ability of biomaterials to form apatite in PBS depends on the heating challenge that fully induces the grain transformation. These results www.scienceasia.org contradict those reported previously, indicating that the formation of bone apatite on fully sintered HA and TCP ceramics has been hardly detectable 31,32 . Indeed, the nature and crystallinity of apatite forming phases depend on various parameters, including concentrations of phosphate/carbonate sources, ionic strength and pH of the soaked solution, and the kinetics of the nucleation and growth processes 33 .…”
Section: Discussioncontrasting
confidence: 87%
“…The ability of biomaterials to form apatite in PBS depends on the heating challenge that fully induces the grain transformation. These results www.scienceasia.org contradict those reported previously, indicating that the formation of bone apatite on fully sintered HA and TCP ceramics has been hardly detectable 31,32 . Indeed, the nature and crystallinity of apatite forming phases depend on various parameters, including concentrations of phosphate/carbonate sources, ionic strength and pH of the soaked solution, and the kinetics of the nucleation and growth processes 33 .…”
Section: Discussioncontrasting
confidence: 87%
“…It is known that silicocarnotite is a calcium silicophosphate with carnotite structure. Some authors determined that the silicocarnotite structure is very similar to hydroxyapatite and examined its in vitro bioactivity [34]. They concluded that the introduction of silicon in HA lattice improved in vitro bioactive response as compared to the apatite without silicon content [34].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors determined that the silicocarnotite structure is very similar to hydroxyapatite and examined its in vitro bioactivity [34]. They concluded that the introduction of silicon in HA lattice improved in vitro bioactive response as compared to the apatite without silicon content [34]. Others suggested that the loss of all -OH from HA due to SiO 4 substitution results in silicocarnotite structure.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of silicon incorporated has an important influence on its thermal stability and phase composition [2,[19][20][21][22][23][24] Magnetron co-sputtering method is used in [25,26] to prepare of SiHA materials with 0.8, 2.2 and 4.9 wt.% silicon content. The in vitro cellular response indicated an increase in the growth of human osteoblast (HOB) cell on the synthesized coatings, along with formation of extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%